2010
DOI: 10.4236/jsea.2010.311121
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Evolutionary Strategy for Synthesis of Analogue Computational Circuits

Abstract: There are very few reports in the past on applications of Evolutionary Strategy (ES) towards the synthesis of analogue circuits. Moreover, even fewer reports are on the synthesis of computational circuits. Last fact is mainly due to the difficulty in designing of the complex nonlinear functions that these circuits perform. In this paper, the evolving power of the ES is challenged to design four computational circuits: cube root, cubing, square root and squaring functions. The synthesis succeeded due to the usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In earlier works, we already had reported about some aspects of DM and adaptation [1,3]. In later works, we found that the system performs better at SRs 10 times lower than before (from 10% to 1%) [3].…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…In earlier works, we already had reported about some aspects of DM and adaptation [1,3]. In later works, we found that the system performs better at SRs 10 times lower than before (from 10% to 1%) [3].…”
Section: Introductionmentioning
confidence: 82%
“…In earlier works, we already had reported about some aspects of DM and adaptation [1,3]. In later works, we found that the system performs better at SRs 10 times lower than before (from 10% to 1%) [3]. Despite proving our recent technique to be a powerful tool in comparison with others [7], we have failed with it when evolving TIMC.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations